Simulation studies of secondary electron yield with electron transport from Cu (110) surfaces containing C2, N2, CO2, or NO2 adsorbates - Maille, M.; Dennis, N. C.; Pokhrel, Y. M.; Sanati, M.; Joshi, R. P. (Frontiers in Materials, 2023)
Secondary electron yields of (110) copper surfaces, covered with either carbon, nitrogen, or their dioxides, have been studied by employing combined first principles methods for the material properties and Monte Carlo simulations for electron transport. In agreement with results observed in studies of secondary electron emission, it is shown that the formation of C2 and N2 monolayers reduce the secondary electron yields, while CO2 and NO2 increase the yield significantly. The physical reasons behind the increase and decrease of the yield for each system from an electronic perspective are discussed. It is demonstrated that in the case of C2 and N2 formation, changes in the surface electronic barrier reduce the probability of electron escape from the Cu surface, resulting in lower secondary electron emission. Formation of CO2 and NO2, on the other hand, reduce the electronic barrier effects. In addition, due to weak bonding of the CO2 layer with the Cu host, the surface provides an additional source of secondary electrons resulting in higher electronic emission yield. Moreover, the NO2 adsorbate creates a surface electric field that changes the surface electron energy and increases the electron escape probability. Furthermore, by studying electron transport inside the Cu system and modeling the power loss taking account of the inelastic electron scattering within the material, changes in the thermal energy of the system have been modeled. It is verified that thermal change in the system is negligible and so during secondary electron emission measurements, negligible (if any) surface adsorption or desorption could occur. Finally, calculated parameters such as the work function and cohesive energy are reported for all surfaces and shown to be in good agreement with available experimental measurements.